2017
DOI: 10.1088/2050-6120/aa5e29
|View full text |Cite
|
Sign up to set email alerts
|

Non-typical fluorescence studies of excited and ground state proton and hydrogen transfer

Abstract: Fluorescence studies of tautomerization have been carried out for various systems that exhibit single and double proton or hydrogen translocation in various environments, such as liquid and solid condensed phases, ultracold supersonic jets, and finally, polymer matrices with single emitters. We focus on less explored areas of application of fluorescence for tautomerization studies, using porphycene, a porphyrin isomer, as an example. Fluorescence anisotropy techniques allow investigations of self-exchange reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 131 publications
2
4
0
Order By: Relevance
“…Secondly, Hydrogen bonds enable proton transfer without barrier crossing, along the Hydrogen bond, resulting in a modified geometry with lower energy in the excited state. Such an effect of proton transfer induced fluorescence was also demonstrated in other molecular systems [26,38]. Our analysis also shows that the mechanism of proton transfer is highly dependent on the formation of specific Hydrogen bonds between the monomers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Secondly, Hydrogen bonds enable proton transfer without barrier crossing, along the Hydrogen bond, resulting in a modified geometry with lower energy in the excited state. Such an effect of proton transfer induced fluorescence was also demonstrated in other molecular systems [26,38]. Our analysis also shows that the mechanism of proton transfer is highly dependent on the formation of specific Hydrogen bonds between the monomers.…”
Section: Discussionsupporting
confidence: 82%
“…Such an effect of proton-transfer-induced fluorescence was also demonstrated in other molecular systems. , Our analysis also shows that the mechanism of proton transfer is highly dependent on the formation of specific HBs between the monomers. Although we demonstrated this phenomenon with a dipeptide that possesses phenyl side groups, the mechanism is clearly dependent on the HBs and not on the aromatic nature of the side groups.…”
Section: Discussionsupporting
confidence: 77%
“…The small values of both S M and Stokes shift indicate the great rigidity of the porphycene core and the overall small difference in the equilibrium position of the S 0 and S 1 potential curves. At 77 K (panel c ), in a frozen glassy matrix of 2‐MeTHF, both the emission and the excitation spectra undergo significant line narrowing with the appearance of rich vibronic structure in the region of the L band absorption which is reflected in the emission vibrational breathing modes [25,26] . At high energy, the Soret band resolves in two distinct peaks.…”
Section: Resultsmentioning
confidence: 99%
“…At 77 K (panel c), in a frozen glassy matrix of 2-MeTHF, both the emission and the excitation spectra undergo significant line narrowing with the appearance of rich vibronic structure in the region of the L band absorption which is reflected in the emission vibrational breathing modes. [25,26] At high energy, the Soret band resolves in two distinct peaks. The emission lifetime at 77 K increases to 12.3 ns and the strong 0-0 overlap is again an evidence of the molecular rigidity.…”
Section: Optical Properties In Solutionmentioning
confidence: 99%
“…The latter concept is illustrated in Figure d with a possible Frank–Condon diagram that involves proton transfer in higher excited states and can lead to multicolor excitation‐dependent FL. The possibility of excited state proton transfer involvement in FL can be observed in a wide range of systems, including GFP. Quantum molecular modeling (DFT and TDDFT simulations) showed that proton transfer can induce gap reduction in several self‐assembled peptide structures …”
Section: Resultsmentioning
confidence: 99%